Dopaminergic enhancement of striatal response to reward in major depression - Admon, Roee (Am J Psychiatry, 2016)
OBJECTIVE: Major Depressive Disorder is characterized by reduced reward-related striatal activation and dysfunctional reward learning, putatively reflecting decreased dopaminergic signaling. The goal of this study was to test whether a pharmacological challenge designed to facilitate dopaminergic transmission can enhance striatal responses to reward and improve reward learning among depressed individuals. METHOD: In a double-blind placebo-controlled design, 46 unmedicated depressed participants and 43 healthy controls were randomized to receive either placebo or a single low dose (50 mg) of the D2/D3 antagonist amisulpride, which was believed to increase dopamine signaling through presynaptic autoreceptor blockade. To investigate the effects of increased dopaminergic transmission on reward-related striatal function and behavior, a monetary incentive delay task (in conjunction with functional magnetic resonance imaging) and a probabilistic reward learning task were administered at absorption peaks of amisulpride. RESULTS: Depressed participants selected previously rewarded stimuli less frequently than controls, indicating reduced reward learning, but this effect was not modulated by amisulpride. Relative to depressed participants receiving placebo (and controls receiving amisulpride), depressed participants receiving amisulpride exhibited increased striatal activation and potentiated corticostriatal functional connectivity between the nucleus accumbens and midcingulate cortex in response to monetary rewards. Stronger corticostriatal connectivity in response to rewards predicted better reward learning among depressed individuals receiving amisulpride as well as among controls receiving placebo. CONCLUSIONS: Acute enhancement of dopaminergic transmission potentiated reward-related striatal activation and corticostriatal functional connectivity in depressed individuals (but had no behavioral effects), suggesting that targeted pharmacological treatments may normalize neural correlates of reward processing in depression. Thus, despite acute effects on neural function, behavioral modification may require more chronic exposure, fitting prior reports that antidepressant effects of amisulpride in depression emerged after sustained administration. CLINICALTRIALS.GOV PROTOCOL: 2010-P001568